Inner Sydney at war : the home front from Sudan to Vietnam - Ross, John W. (John Walter), 1946- (Surry Hills, N.S.W. : John W. Ross, 2024)
"When a country commits itself to a war overseas in aid of an ally or in its own defence, the support of those at home is vitally important in maintaining the morale of troops at the front, assisting the families of soldiers, and funding the huge expense incurred by the nation. This history of the home front during wartime draws examples from inner Sydney and suburbs such as Surry Hills, Darlinghurst and Moore Park, where the mixture of residences, industries and the proximity to places of strategic importance make it fairly representative of an urban environment in times of war."--Foreword, p. 1.
Mode of access : Available online.
Keywords: Korean War, 1950-1953 -- Australia; Malaboch War, South Africa, 1894.; Vietnam War, 1961-1975 -- Australia; World War, 1914-1918 -- Australia; World War, 1939-1945 -- Australia; Military history; Australia -- History, Military; Sydney (N.S.W) -- Social conditions -- 20th century; Sydney (N.S.W) -- Social life and customs -- 20th century; Electronic books